Culture, legal heritage and the regulation of labor - Ang, James B. (2019)
According to cross-cultural psychologists, cross-country differences in individualism vs. collectivism constitute an important dimension of cultural variation. Legal-economic theorists argue that legal philosophies such as common law and civil law have developed differently over centuries and have persistent effects. In this paper, we argue that the effects of culture and institutions should not be analyzed in isolation from each other, as this disregards their interactions. We merge the two separate literatures on cultural attributes and legal origin theories, and derive a hypothesis regarding their joint effects on labor market regulations. We hypothesize that the effect of individualism on the political determination of labor regulations should be particularly pronounced in more market-oriented economic systems (as in British common law countries) compared to more rigid and bureaucratic state-centered systems (as in French civil law countries). Market oriented economies give individual effort and ability greater room to flourish, which in individualistic cultures yields weaker labor regulations. The effect of individualism should be smaller in state centered systems. Using data on the average rigidity of labor regulations during the years 1950-2004 in 86 countries, we find that the negative effect of individualism on the rigidity of labor regulations is enhanced by the presence of a common law legal system. In fact, individualism has no effect on the rigidity of labor market regulations in civil law countries. Analogously, the negative effect of common law legal origin on labor market regulations is found to be conditional on the level of individualism. Individualism and common law legal systems are complements in the determination of labor regulations.